Potentiometric Titrations of Para and Nitro Substituted Aromatic Acids and their Mixtures in Methylethylketone - Ozeroglu, Cemal; Karahan, Mesut (CHEM SOC PAKISTAN, 2011)
In this study, it was the purpose to examine the potentiometric titrations of para and nitro substituted aromatic acids in methylethylketone (MEK) as a non-aqueous solvent. Good analytical results were obtained in determining the amount of each acid and the amounts of acids in their ternary mixtures by using 0.0964 N tetrabuthylammoniumhydroxyde (TBAH) as a standard titrant. Methylethylketone (MEK) which is a good solvent for many organic compounds and has a convenient liquid range of -86 to 80 degrees C was used for titration of the para and nitro substituted aromatic acids. A linear relationship has been found between pK(a) values of the para and nitro substituted aromatic acids in water and the half neutralization potential (HNP) values determined by potentiometric titration curves of the same acids in MEK.
Keywords: DICARBOXYLIC-ACIDS; PK(A) VALUES; WEAK ACIDS; PYRITE; WATER; Chemistry